The impact of donor liver allograft fibrosis on patients undergoing liver transplantation. Issue 3 (11th February 2018) - Wadhera, Vikram; Harimoto, Norifumi; Lubezky, Nir; Gomatos, Ilias; Facciuto, Matias; Gonzalez, David; Stueck, Ashley; Fiel, Maria Isabel; Schiano, Thomas; Facciuto, Marcelo E.
Abstract: Background: The utilization of extended criteria liver allografts (ECD) shortens time to transplantation. Objective: To characterize the effect of liver allograft fibrosis on graft and patient survival after liver transplantation (LT), with particular attention to fibrosis progression. Methods: Retrospective database search of donor and recipient liver allograft histology of liver transplants performed between 2007 and 2011. Donor and patient characteristics were analyzed. Results: One hundred and one patients underwent LT with donor liver allografts with early‐stage fibrosis (stage 1 fibrosis and stage 2 fibrosis). The level of liver fibrosis did not progress in 40% of the patients tested, and there was a regression of fibrosis in 30%. At a median follow‐up of 71 months, of 101 patients transplanted with fibrotic livers, 63 patients (63%) were alive with functioning initial grafts, six patients (6%) were retransplanted, and 35 patients expired. The graft survival rates were 82% and 69% at 1 and 5 years, respectively. Graft survival differences were not found to be statistically significant between the degrees of liver allograft fibrosis: 5‐year graft survival (73% for stage 1 fibrosis and 62% for stage 2 fibrosis, P = .24). The entire fibrosis group was further compared with a control group of 208 consecutive primary liver transplant patients with allografts having no fibrosis. The 5‐year graft survival was not significantly different between the groups (69% for the fibrosis group vs 75% for the nonfibrosis group, P = .19). Survival was also not statistically different between the groups (5‐year survival of 73% for the fibrosis group vs 79% for the nonfibrosis group, P = .2). In patients with HCV, graft survival differences were not found to be statistically significant with the use of early‐stage fibrotic livers: 5‐year graft survival of 60% for fibrosis group vs 70% for the nonfibrosis group, P = .22). Conclusion: This study demonstrates that allografts with early‐stage fibrosis achieve acceptable long‐term survival after liver transplantation. Given these preliminary results, the use of organs with early‐stage fibrosis warrants further studies at a larger scale to validate these results.